Stable Potassium Metal Anodes with an All‐Aluminum Current Collector through Improved Electrolyte Wetting. Issue 49 (2nd November 2020) - Liu, Pengcheng; Wang, Yixian; Hao, Hongchang; Basu, Swastik; Feng, Xuyong; Xu, Yixin; Boscoboinik, Jorge Anibal; Nanda, Jagjit; Watt, John; Mitlin, David
Abstract: This is the first report of successful potassium metal battery anode cycling with an aluminum‐based rather than copper‐based current collector. Dendrite‐free plating/stripping is achieved through improved electrolyte wetting, employing an aluminum‐powder‐coated aluminum foil "Al@Al, " without any modification of the support surface chemistry or electrolyte additives. The reservoir‐free Al@Al half‐cell is stable at 1000 cycles (1950 h) at 0.5 mA cm −2, with 98.9% cycling Coulombic efficiency and 0.085 V overpotential. The pre‐potassiated cell is stable through a wide current range, including 130 cycles (2600 min) at 3.0 mA cm −2, with 0.178 V overpotential. Al@Al is fully wetted by a 4 m potassium bis(fluorosulfonyl)imide‐dimethoxyethane electrolyte (θCA  = 0° ), producing a uniform solid electrolyte interphase (SEI) during the initial galvanostatic formation cycles. On planar aluminum foil with a nearly identical surface oxide, the electrolyte wets poorly (θCA  = 52° ). This correlates with coarse irregular SEI clumps at formation, 3D potassium islands with further SEI coarsening during plating/stripping, possibly dead potassium metal on stripped surfaces, and rapid failure. The electrochemical stability of Al@Al versus planar Al is not related to differences in potassiophilicity (nearly identical) as obtained from thermal wetting experiments. Planar Cu foils are also poorly electrolyte‐wetted and become dendritic. The key fundamental takeaway is that the incomplete electrolyte wetting of collectors results in early onset of SEI instability and dendrites. Abstract : Dendrite‐free electrochemical cycling of potassium metal anodes is achieved through improved electrolyte wetting on a geometrically rough all‐aluminum current collector. The electrolyte was standard potassium bis(fluorosulfonyl)imide‐dimethoxyethane and no modifications were made to the collector surface chemistry. The key takeaway from this study is that good electrolyte wetting is necessary for stable plating/stripping, with poor wetting ensuring instability and dendrite growth.